The relationship of four variants of the Vocabulary Size Test to a criterion measure of meaning recall vocabulary knowledge. (December 2019) - Stoeckel, Tim; Stewart, Jeffrey; McLean, Stuart; Ishii, Tomoko; Kramer, Brandon; Matsumoto, Yuko
Abstract: The Vocabulary Size Test (VST) was designed to measure the vocabulary needed for reading. Recent research, however, has questioned the "meaning-recognition" construct measured by the VST, arguing that "meaning-recall" is a more accurate estimate of reading vocabulary. The present study compared four variants of the VST to determine which, if any, could be used as an expedient proxy for estimating meaning-recall knowledge. Two hundred Japanese university students completed a criterion meaning-recall measure of VST target words and one of four randomly-assigned VST variants: monolingual, monolingual with an "I don't know" option (IDK), bilingual, or bilingual with IDK. The bilingual+IDK variant (r = .77) had a significantly lower correlation with the meaning-recall measure than the other three versions (r = .88 to .91). The lower r-value for the bilingual+IDK version appears to have been caused by pronounced differences in IDK use among learners who sat that version of the test. The study concludes that other variants could effectively be used to rank or group learners by meaning-recall knowledge. However, for estimates of reading vocabulary size, measures of meaning-recall should be used, or raw VST scores need to be adjusted to account for differences between VST and meaning-recall scores.